2021
DOI: 10.1108/bfj-05-2021-0476
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of food safety management system implementation in global supply chains

Abstract: PurposeThe study sets to summarise managerial requirements, analyse practices and tools to measure food safety management system (FSMS) implementation. Also, underpinned by critical success factors (CSFs) theory, the authors explore when food firms manage FSMS and which factors are critical to their implementation to identify promising research directions for researchers and suggestions for practitioners through a comprehensive analytical lens.Design/methodology/approachIt is difficult to ensure food safety fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Lastly, effective food safety administration is critical, especially in the agri-food sector, for achieving sustainability and climate goals. Efficient production and distribution practices that ensure food safety can help minimise waste and resource misuse, which are key elements in reducing the environmental impact and advancing towards climate neutrality (Nguyen and Li, 2021).…”
Section: Relationships Between Thementioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, effective food safety administration is critical, especially in the agri-food sector, for achieving sustainability and climate goals. Efficient production and distribution practices that ensure food safety can help minimise waste and resource misuse, which are key elements in reducing the environmental impact and advancing towards climate neutrality (Nguyen and Li, 2021).…”
Section: Relationships Between Thementioning
confidence: 99%
“…Prior studies showed that there is a research gap in understanding the quantifiable relationship between CSFs, such as top management support, human resource management, infrastructure, integration, external assistance, and food safety administration with the firm's performance in achieving climate neutrality and sustainability (Abbas et al ., 2022, 2023a, b; Yontar, 2023; Nguyen and Li, 2022; King and King, 2020). While studies individually address aspects like the effectiveness of Food Safety Management Systems (FSMS) in global supply chains (Duong et al ., 2023; Nguyen and Li, 2021), the role of advanced digital technologies in agri-food supply chains (Yontar, 2023), and strategies for reducing waste (Abbas et al ., 2023a), they fall short in explicitly linking these CSFs to the specific goal of climate neutrality within firms. Particularly, the impact of these factors on a firm's carbon footprint, sustainable practices, and overall environmental impact remains underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is likely to be related to food sectors in developing countries like China and Vietnam, where consumers are usually doubtful of their trustworthiness (Rodrigues et al, 2019). Consequently, food businesses require more concrete evidence from their suppliers to convince their customers (Nguyen and Li, 2022b). Certainly, customers profit more from the availability of higher quality food, but businesses have been indirectly pushed to implement multiple assurance procedures, which are costly and their effectiveness are often questionable (Trienekens and Zuurbier, 2008).…”
Section: Suppliers Of Well-performed Food Businessesmentioning
confidence: 99%
“…However, even if the adoption of new technology can impact significantly on food safety management systems and protect consumer health in global food supply chain its implementation still requires more investigation and future works (Nguyen & Li, 2021). Consumers appear to be unaware of smart tags as highlighted by research conducted within the EITFOOD SMART TAGS project (https://www.eitfood.eu/ projects/smart-tags-for-improving-consumer-interaction-in-food-valuechain-2020).…”
Section: Implications For Consumers Retailers and Food Processorsmentioning
confidence: 99%